Ambulatory surgery - Estapé Carriquiry, Gonzalo (Cirugía del Uruguay, 2002)
A major outpatient surgery is one in which the patient, regardless of the type anesthesia used, requires little care postoperative, does not require hospital admission and can be discharged a few hours later of the intervention. Its development in recent years has been dizzying, which is translated into the figures obtained in the United States: in 1984 it was used in the 28% of cases (400,000 operations), while that in 1990, it went to 50%; SMG Marketing Group of Chicago, estimates an increase of 14% for the year that passes.